Indexing PXRD structural parameters of graphene oxide-doped metal-organic frameworks - Kamal, K. (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
A family of metal-organic framework, Mg 3O3(CO2)3â nanocrystallites which are also known as Mg-MOF-74, were synthesized by solvothermal method at high temperature under autogenous pressure. The graphene oxide was embedded into the framework via in-situ synthesis method to form a composite structure of Mg-MOF-74@nGO. n was varied from 0.1 to 0.6 wt% of the weight of pristine material. The synthesized samples were examined under Powder X-Ray Diffraction analysis to affirm their crystalline structure. Further studies were conducted by indexing the lattice parameters of the hexagonal crystals. The volume of unit cell and Scherrerâs crystallite size were also determined to study the effect of GO loading amount on their grown dimensions. The results showed that the presence of GO in the range of 0.1-0.6 wt% did not influence the dimension of the crystal except a slight expansion in vertical direction with the increment of GO loading. Â© BEIESP.